Drummondin E and Flinderole B are potential inhibitors of RNA-dependent RNA polymerase of SARS-CoV-2: an in silico study - Nahid Akhtar; Himanshu Verma; O.M. Silkari; Atul K. Upadhyay; Vikas Kaushik; M. Amin-ul Mannan (BioTechnologia, 2022)
Coronavirus disease 2019 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has affected 235.6 million people worldwide. In the present study, RNA-dependent RNA polymerase (RdRp) (PDB Id: 6M71) of SARS-CoV-2, an essential enzyme needed for subgenomic replication and amplification of RNA, was selected. Similar to other RdRps, it is a conserved protein and a popular target for antiviral drug therapy. Based on a com puta tional approach, potential RdRp inhibitors were identified. The absorption, distribution, metabolism, ex cretion, and toxicity (ADMET) of selected molecules were determined using computation tools. The potential inhibitors were docked to the RdRp and later confirmed by Molecular Dynamics (MD) using the “Flare” module of Cresset software. Drummondin E and Flinderole B had higher drug similarity scores among the compounds selected in this study. Both these compounds are noncarcinogenic, nonirritant, nontumorigenic, and non muta genic. Molecular docking studies showed that both compounds can bind to RdRp. The best ligand interaction pat terns were validated by MD using the “Flare” module. MD was performed for the period of 100 ns with the time step of 1 fs. The simulation results suggest that Thr-680, Arg-624, Lys-676, and Val-557 are key interacting part ners in the Drummondin E-RdRp complex, while Asp-618, Asp-760, Asp-623, Arg-624, and Asp-761 are the inter acting partners in the Flinderole B-RdRp complex. Based on the in silico drug-likeness score; ADMET properties; and molecular simulation result, we surmise that Flinderole B and Drummondin E could impede SARS-CoV-2 genome replication and transcription by targeting the RdRp protein.